(untitled) (Journal of Sciences & Technology, 2016)
This paper summarizes a numerical study of the effects of buoyancy ratio on double-diffusive natural convection in square inclined cavity filled with fluid saturated porous media. Transverse gradients of heat and solute are applied on the two horizontal walls of the cavity, while the other two walls are impermeable and adiabatic. The Darcy model with the Boussinesq approximation is used to solve the governing equations. The flow is driven by a combined buoyancy effect due to both temperature and concentration variations. A finite volume approach has been used to solve the non-dimensional governing equations. The results are presented in streamline, isothermal, iso-concentration, Nusselt and Sherwood contours for different values of the non-dimensional governing parameters.